1986
DOI: 10.1152/jappl.1986.61.3.982
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bacterial endotoxin on protecting copper-deficient rats from hyperoxia

Abstract: The administration of very low doses of bacterial endotoxin protects rats during exposure to hyperoxia and is associated with the induction of lung antioxidant enzyme activities. Copper-deficient rats have increased susceptibility to O2 toxicity, which may be related to their decreased lung superoxide dismutase activity (SOD) or decreased plasma ceruloplasmin concentrations. To determine whether endotoxin can protect against hyperoxia in this susceptible model, we exposed copper-deficient and control rats to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1988
1988
1998
1998

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Similar to the ethanol-exposed fetus, this phenomenon is probably a protective response to the generation of free radicals resulting from ethanol metabolism. Similar to ADR and alcohol, other potential free radical generators whose toxicity has been reported to be increased under conditions of Cu deficiency include carbon tetrachloride and hyperoxia (37,42). Thus, whereas this is still an evolving area of research, current evidence supports the idea that the toxicity of compounds that produce free radicals via their metabolism are enhanced under conditions of Cu deficiency owing to an impairment in the antioxidant system.…”
Section: Functional Significance Of Cu Deficiency-induced Changes In mentioning
confidence: 98%
“…Similar to the ethanol-exposed fetus, this phenomenon is probably a protective response to the generation of free radicals resulting from ethanol metabolism. Similar to ADR and alcohol, other potential free radical generators whose toxicity has been reported to be increased under conditions of Cu deficiency include carbon tetrachloride and hyperoxia (37,42). Thus, whereas this is still an evolving area of research, current evidence supports the idea that the toxicity of compounds that produce free radicals via their metabolism are enhanced under conditions of Cu deficiency owing to an impairment in the antioxidant system.…”
Section: Functional Significance Of Cu Deficiency-induced Changes In mentioning
confidence: 98%
“…https://doi.org/10.1079/PNS19920039 The question of whether deficiencies in trace elements interfere with the production of these proteins during inflammation has been addressed in any detail only for Cu and Zn. The ability of rats to increase plasma caeruloplasmin and Cu-Zn superoxide dismutase in lung, in response to the dual stress of endotoxin and high oxygen concentrations, is impaired by Cu deficiency (Spence et al 1986). Likewise the ability of IL-1 to increase plasma concentrations of fully functional CP is also suppressed (Barber & Cousins, 1988).…”
Section: Modulatory Effects Of Micronutrientsmentioning
confidence: 99%
“…This means that in the selenium-deficient animal mechanisms other than antioxidant enzyme induction provide early protection from hyperoxia. Copper-deficient rats could not increase lung concentrations of copper and zinc SOD, but lung manganese SOD concentrations were found to be induced by endotoxin [27]. Block [81] found that rats pretreated with endotoxin had significantly reduced mortality during exposure to hyperoxia and were also protected against hyperoxia-induced injury to the pulmonary capillary endothelium, which is manifested by depression of amine uptake (p < 0.05).…”
Section: Modification Of Oxygen Ins'wrymentioning
confidence: 99%
“…Copper-deficient animals have decreased lung activity of the copper and zinc form of SOD and also exhibit increased susceptibility to oxygen lung damage [26,27]. Vitamin E deficiency in rats has been shown to increase the toxic effects of oxygen [28].…”
Section: Radical Damagementioning
confidence: 99%
See 1 more Smart Citation